Influence of Exercise Intensity on Ventilation During Constant Load Exercise Test in Sedentary Male Subjects - Ugur, Fethi Ahmet; Algul, Sermin; Ozcelik, Oguz (Wiley-Blackwell, 2016)
[Abstract Not Available]